VD_FINDINFO Jug / 2011 / 222 vom 4. Mai 2011 - VD Tribunal cantonal (2011)
VOIES DE FAIT, INJURE, MENACEDROIT PÉNAL, PRÉSOMPTION D'INNOCENCE | 126 al. 1 CP, 177 al. 2 CP, 177 CP, 180 al. 1 CP, 433 al. 3 CPP (CH)